Characteristics of landing impact in athletes who have not returned to sports at the pre-injury competition level after anterior cruciate ligament reconstruction - Shunsuke Ohji; Junya Aizawa; Kenji Hirohata; Takehiro Ohmi; Sho Mitomo; Tetsuya Jinno; Hideyuki Koga; Kazuyoshi Yagishita (Elsevier, 2021)
Background: Most patients with anterior cruciate ligament (ACL) injury undergo ACL reconstruction (ACLR) with the expectation of being able to return to sport (RTS) at the same level of the competition as before the injury. The magnitude and asymmetry of landing impact are important post-ACLR functional variables related to increased ACL strain and poor athletic performance. However, the association between the RTS status and landing impact in post-ACLR patients is unknown. Objective: To investigate the association between RTS status and landing impact during single-leg landing in post-ACLR patients. Methods: Forty-four patients after primary, unilateral ACLR participated in this study. They had already participated in sports post-ACLR. Questionnaires were used to assess whether the participants achieved the same competitive level of RTS as before the injury. The magnitude and symmetry of the peak vertical ground reaction force (pVGRF) were collected and analysed during single-leg jump landings. Additionally, knee functions (range of motion, laxity, effusion, strength, and single-leg hop distance) were measured. Results: A total of 28 (64%) patients reported RTS at their pre-injury competition levels. The no-RTS group had a lower pVGRF magnitude on the operated side than the yes-RTS group (P = .019). The no-RTS group had a higher rate of pVGRF asymmetry (50%) than the yes-RTS group (18%) (P = .040). Logistic regression analysis revealed that pVGRF magnitude and asymmetry were significantly associated with the RTS status. Logistic regression analysis adjusted for knee function revealed that the pVGRF magnitude was significantly associated with the RTS status. Conclusion: In patients who are unable to RTS at their pre-injury competition level after ACLR, the pVGRF is lower and more likely to be asymmetrical than in those able to RTS at their pre-injury competition level.